Prenatal stress and its association with amygdala-related structural covariance patterns in youth - Mareckova, Klara; Miles, Amy; Liao, Zhijie; Andryskova, Lenka; Brazdil, Milan; Paus, Tomas; Nikolova, Yuliya S (NeuroImage. Clinical, 2022)
BACKGROUND: Prenatal stress influences brain development and mood disorder vulnerability. Brain structural covariance network (SCN) properties based on inter-regional volumetric correlations may reflect developmentally-mediated shared plasticity among regions. Childhood trauma is associated with amygdala-centric SCN reorganization patterns, however, the impact of prenatal stress on SCN properties remains unknown. METHODS: The study included participants from the European Longitudinal Study of Pregnancy and Childhood (ELSPAC) with archival prenatal stress data and structural MRI acquired in young adulthood (age 23-24). SCNs were constructed based on Freesurfer-extracted volumes of 7 subcortical and 34 cortical regions. We compared amygdala degree centrality, a measure of hubness, between those exposed to high vs. low (median split) prenatal stress, defined by maternal reports of stressful life events during the first (n = 93, 57% female) and second (n = 125, 54% female) half of pregnancy. Group differences were tested across network density thresholds (5-40%) using 10,000 permutations, with sex and intracranial volume as covariates, followed by sex-specific analyses. Finally, we sought to replicate our results in an independent all-male sample (n = 450, age 18-20) from the Avon Longitudinal Study of Parents and Children (ALSPAC). RESULTS: The high-stress during the first half of pregnancy ELSPAC group showed lower amygdala degree particularly in men, who demonstrated this difference at 10 consecutive thresholds, with no significant differences in global network properties. At the lowest significant density threshold, amygdala volume was positively correlated with hippocampus, putamen, rostral anterior and posterior cingulate, transverse temporal, and pericalcarine cortex in the low-stress (p(FDR) < 0.027), but not the high-stress (p(FDR) > 0.882) group. Although amygdala degree was nominally lower across thresholds in the high-stress ALSPAC group, these results were not significant. CONCLUSION: Unlike childhood trauma, prenatal stress may shift SCN towards a less amygdala-centric SCN pattern, particularly in men. These findings did not replicate in an all-male ALSPAC sample, possibly due to the sample's younger age and lower prenatal stress exposure.
Keywords: Amygdala; longitudinální studie; ELSPAC; Prenatal stress; ALSPAC; těhotenství; hipokampus; mladiství; amygdala; mužské pohlaví; Structural covariance; mozek; Adult; mladý dospělý; dítě; Child; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Brain; Young Adult; ženské pohlaví; Humans; Degree centrality; Pregnancy; Longitudinal Studies; dospělí; Female; Adolescent; lidé; Male; Hippocampus